Self-Reported Offending in the United States and Malaysia: Does East Meet West? - Hartley, Richard D. (International journal of offender therapy and comparative criminology, 2021)
To date, international comparisons of self-reported crime have been mostly limited to Western countries. The current study explores offending for large samples of university students in Malaysia (N = 2,058) and the United States (N = 2,511), and utilizes measures of social bond theory to test its predictive utility cross-nationally. The descriptive results reveal that for both males and females, offending rates were substantially higher in the United States, often 3 to 4 times higher. Rare events logistic regression results reveal not only some support for our measures of the social bond constructs in both countries but also that there are significant cross-country differences in the correlates of offending. Partitioned regression models suggest these differences vary considerably by type of crime, and that some of the significant correlates of offending are similar cross-nationally but that unique predictors emerge by country dependent on the offense in question. Offending in the U.S. sample appears to be more closely linked to breakdowns in family structure (parental divorce, single parenthood), whereas for the Malaysian sample, parental income and respondent’s education level seem to be more closely linked to offending. The current study provides one of just a few comparative studies between a Western country and an Asian country based on self-reported data. Such data can provide a useful cross-check of international comparisons based on official data. Methodologically, implications are that the self-report survey method continues to be a fruitful avenue for exploration of cross-national offending.